Development of plaster foam for thermal and acoustic applications. (30th November 2020) - Arroyo, F.N.; Christoforo, A.L.; Salvini, V.R.; Pelissari, P.I.B.G.B.; Pandolfelli, V.C.; Luz, A.P.; Cardoso, C.A.
Highlights: Microsilica increase mechanical properties without affect acoustic properties. Higher microsilica percentage, impact in a porosity smaller. With 5% of microsilica, better is the thermal conductivity. It is possible to obtain a 87.85% of porosity with 0.20% of microsilica. Abstract: Gypsum is an ancient material of great abundance that can be used as acoustic and thermal insulation protection in civil construction, especially when water-based foam is added to it, improving these properties. This research presents gypsum foam processing using a direct casting method with additives from natural sources, thus avoiding environment degradation. The results showed that gypsum foam has a potential for thermal and acoustic insulation and is more effective than other materials currently being used. Although, the material mechanical strength decreases when only water-based foam is added, further microsilica (MS) addition improved its mechanical strength without spalling its acoustic absorption and thermal conductivity.